Evaluation Of Antibiotic Use In Sepsis Patients In The ICU Treatment Room, Gatot Soebroto Rspad Period January 2020–December 2021 - Ria Anggraeni; Wawaimuli Arozal; Yati Sumiyati; Marliana Sri Rejeki (Jurnal Ekonomi, 2024)
Hypertension is Sepsis is a systemic inflammatory response syndrome caused by infection. Globally, the incidence of sepsis has increased with increasing mortality. Antibiotics used appropriately are considered to reduce mortality in sepsis. Destination of this study was to evaluate the use of antibiotics in septic patients in room care Gatot Army Hospital ICU Soebroto by qualitative with method old nor quantitative with method ATC / DDD. Method : Study this is study descriptive analytic and data collection is done retrospectively. The study was conducted by looking at the medical records of patients receiving antibiotic therapy who were treated at the hospital room Gatot Army Hospital ICU Soebroto period January 2020- December 2021. Results : Between 97 patient, 63 patient of them are male ( 64.9 %) and 34 patient Others are female ( 35.0 %). The highest age range is in the age of > 65 as many years ( 43.3 %). d result From the evaluation of the quality of antibiotics, it was found that the use of antibiotics was appropriate k (79%), possible appropriate (20.4%) and no exactly as much (0.52%). while the quantity of antibiotic use is obtained in total DDD/100 patient day take care as much 326.52 with antibiotics the most is usage meropenem 97.75 DDD/100 patient-day take care.